Pemanfaatan Isi Rumen Sapi Sebagai Substitusi Dedak pada Pembuatan UMB (Urea Mollasses Block) untuk Pakan Sapi di Kelompok Tani Jaya Abadi Desa Larangan dalam Pamekasan - Hidayati, Nurul; Riszqina, Riszqina; Agustina, Desi Kurniati (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This devotion aims to utilise cow rumen contents as a substitute for bran in making Urea Molasses Blok (UMB), which is used as additional feed for the Jaya Abadi Farmer Group, Larangan Dalam Village, Pamekasan Regency. The form of community service activities are: (1) train participants' skills to be able to make UMB products; (2) produce UMB products as a business product for the Farmer group. The activity consists of three stages, namely (1) preparation of service activities; (2) preparation of UMB training activities; (3) training in making UMB rumen contents. The extension activities were attended by 20 participants, consisting of 55% women and 45% men. The participants owned 55% goats and 45% cows, so the training results were expected to be developed. The results of the training on making UMB from rumen contents have provided additional knowledge to members of the Jaya Abadi Farmer Group. In conclusion, the evaluation results after the UMB making training, there is a very real increase in the understanding of the training participants on how to make UMB and its utilisation for livestock.